Effect of Source-Detector Distance on the Measurement of Hemoglobin Using Near-Infrared Spectroscopy in Breast Cancer. (19th July 2019) - Hayashi, Maho; Yoshizawa, Nobuko; Ueda, Yukio; Mimura, Tetsuya; Ohmae, Etsuko; Yoshimoto, Kenji; Wada, Hiroko; Nasu, Hatusko; Ogura, Hiroyuki; Sakahara, Harumi
We measured total hemoglobin concentrations in breast tumors by near-infrared time-resolved spectroscopy. Muscles interfere with measurement when the probe is close to the chest wall. Since the target area of measurement depends on the distance between the light source and probe detector, we inferred that this issue could be solved by reducing the source-detector distance. The purpose of this study was to examine the effects of the source-detector distance on the measurement of total hemoglobin concentration in the breast. We examined 26 patients with breast tumors. Total hemoglobin concentration was measured in tumors and the contralateral normal breasts at source-detector distances of 20 and 30 mm. The difference in total hemoglobin concentration between each tumor and the contralateral breast was calculated. The normal breast total hemoglobin concentration was significantly smaller for the source-detector distance of 20 mm than for the source-detector distance of 30 mm. Differences in source-detector distance did not significantly affect tumor total hemoglobin. The difference in total hemoglobin concentration between the tumor and the contralateral breast obtained at the source-detector distance of 20 mm was significantly higher than that obtained at the source-detector distance of 30 mm. From these results, we considered that measurement with a source-detector distance of 20 mm is less affected by the chest wall than with a source-detector distance of 30 mm and that the difference in total hemoglobin concentration between the tumor and the contralateral breast at a source-detector distance of 20 mm can better reflect the net total hemoglobin concentrations of the breast tumors. In conclusion, using a probe with a source-detector distance of 20 mm can more accurately evaluate the total hemoglobin concentration in breast tumors.